Efecto de sistemas de sangría sobre la productividad de Hevea brasiliensis en el Magdalena Medio Santandereano - Rojas Molina, Jairo; Rojas Buitrago, Mervin Andrés; Rueda, Gustavo Hernando; Jaimes Suárez, Yeirme; Luiz Furtado, Edson (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Páginas 184-192.